The persuasive power of campaign advertising - Ridout, Travis N., 1974- (Temple University Press, 2011)
The Persuasive Power of Campaign Advertising offers a comprehensive overview of political advertisements and their changing role in the Internet age. Travis Ridout and Michael Franz examine how these ads function in various kinds of campaigns and how voters are influenced by them. The authors particularly study where ads are placed, asserting that television advertising will still be relevant despite the growth of advertising on the Internet. The authors also explore the recent phenomenon of outrageous ads that "go viral" on the web-which often leads to their replaying as television n